The predictive value of dyadic coping in the explanation of PTSD symptoms and subjective well-being of work accident victims - Lameiras, Susana (2018)
Objective: Work accidents may be considered dyadic stressors in so far as they not only affect the worker, but also the couple's relationship. Dyadic coping, as the process by which couples manage the stress experienced by each partner, can strengthen individual health and well-being as well as couple relationship functioning. Accidents at work have progressively been studied from a perspective that focuses on their negative effects on PTSS, anxiety, and depression. However, to a large extent, the dyadic coping processes and results following a work accident are still to be identified and clarified. In this study, we examined the predictive value of dyadic coping in the explanation of PTSS and subjective well-being of work accident victims. Method: This study comprised a sample of 62 individuals involved in work accidents within the last 24 months (61.3% males) and their partners (N = 124; M = 46.25 years, SD = 11.18). All participants responded to the Dyadic Coping Inventory and the work accident victims also answered the PTSD Checklist - Civilian (PCL-C) and the Mental Health Continuum - Short Form (MHC-SF). Two hierarchical multiple regression analyses were performed using two different variable set models: Model 1 comprised the control variables gender and age, and Model 2 included the workers' and the partners' dyadic coping variables. Results: Results showed that dyadic coping reported by both workers and their respective partners (Model 2) was a significant predictor of workers' PTSS (p < 0.01) and subjective well-being (p < 0.001), explaining 31.2% of the variance in PCL-C and 68.7% in MHC-SF results. More specifically, the partners' supportive dyadic coping (by the self) and delegated dyadic coping (by the partner) were significant predictors of the workers' lower PTSS and virtually all the dyadic copying strategies of both the workers' and their partners' were significant predictors of the workers' higher subjective well-being. Conclusion: Dyadic coping of both the workers and their partners predicts the workers' PTSS and subjective well-being. These findings point to the need to work with couples who have experienced a work accident, with a view to improving the workers' mental health outcomes.